SEKSUALITAS PADA PASIEN CA MAMAE YANG MENJALANI KEMOTERAPI - Dian Nur adkhana Sari; Eka Oktavianto (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: One of the treatments for Ca mamae is chemotherapy. This action will indirectly affect sexuality in Ca mamae patients undergoing chemotherapy, which is often felt is irritation and dryness in the vagina, dyspareunia, decreased sexual desire.Objective to find an overview of sexual function and sexual satisfaction of Ca mamae patients undergoing chemotherapy.Methods: This research method is quantitative descriptive cross sectional approach. The number of samples in this study were 31 respondents who underwent chemotherapy, sampling with purposive sampling technique.Results the results of this study showed that most of the sexual function disorders suffered sexual dysfunction as much as 93.5%, and there was a picture of sexual satisfaction with a mean value of 133 with a maximum value of 171 and a minimum of 100, where the lowest domain was the communication domain.Conclusion: Most Ca Mamae patients undergoing chemotherapy experience sexual function disorder.